Innovation in Energy-Saving Houses and a Competitive Advantage in Home Building Business: A Case Study of CoolHouse Company - Udomsamak, Pichet (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2014)
The business of home building is currently under fierce competition due to accelerated growth in order to accommodate the AEC (Asean Economic Community) trade liberalization. All players need to increase their business competitiveness, therefore it is very important to have management guidelines and a personal innovative strategy to gain a competitive advantage. Cool House company is an organization that utilizes an innovative or advanced technology with an energy-efficient building structure to create a competitive advantage. This is done by defining new features, products and services, and distinctive methods of construction by insulating with polystyrene foam in all parts of the concrete wall, floor and roof. According to the Thai Industrial Standard (TIS 1859-2542), Polystyrene foam, is a foam that can be ignited but is non-flammable. Its features are highly-efficient thermal resistance and also noise protection. The house with noise-protection and heat protection from the outside into the building acts like a virtual water cooler. The company has cooperated with the government and private agencies, such as King Mongkut's University of Technology Thonburi and the Asian Institute of Technology, in research and development. Cool House buildings meet the requirements of the Thai energy-saving Act to promote energy conservation and the U.S. Green Building Council. Cool House company is an enterprise applying an energy-efficient innovation to create its distinctiveness and make a big different from its competitors. It meets government policy in energy savings as well.